Effectiveness of promotional strategies of selected hotels in Digos City - Guinang, Vanessa Pearl; Bantilan, Harah Mae C.; Bulado, Maricar P. (--Digos City: UM Digos College, 2016)
The study aimed to determine the effectiveness of promotional strategies of selected hotels in Digos City. Descriptive method was used by collecting through validated survey questionnaries the which were distributed to 300 respondents Digos City. Result on the profile of respondents reveal that the level of effectiveness on promotional strategies of the selected hotels in Digos City in terms of advertising and sales promotion is both high. The level effectiveness of the promotional strategies of the selected hotels in Digos City is high. The level of respondents in terms of the level of effectiveness of the promotional strategies is high. There is no significant difference in the level of effectiveness of the promotional strategies in terms of Gender, age and occupation.